Design and Implementation of a Power Supply for Hearing Aids Based on Human Thermal Energy - Ahmed Mutasim; Mowafag Hassan; Ashgan M. Omer; Kamal R. Doud (University of Khartoum Engineering Journal, 2025)
This paper presents a prototype of a thermoelectric harvester generator designed to convert the waste heat generated by the human body (specifically, the skin) into electrical energy, which.can be used to power a hearing aid unit using renewable energy. The method used for harvesting thermal energy from the human body is based on the principles of the Peltier effect, which is a type of thermoelectric effect. The proposed model consists of three main components: generation, amplification, and hearing aid. The required number of Peltier elements and the skin area have been specified. Additionally, the results demonstrate that the generated energy is influenced by the device’s placement on the body and ambient temperature. Additionally, the results demonstrate that the generated energy is influenced by the system’s location on the human body and the ambient temperature